Levels of reported financial result and the scope of accrual-based earnings management. An exemplification studies on the example of public companies of the clothing industry - Michał Comporek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2023)
The reported values ​​of the financial result at various levels of the company's operations are an important source of information for various stakeholder groups of textile companies. However, due to its accrual character, financial result is a category highly susceptible to intentional increasing (lowering), in line with the diversified premises of the management staff. The objective of the paper is to investigate the relationship between the profitability of textile companies listed on the Warsaw Stock Exchange and the directions and scale of accounting-type earnings management. The obtained results of empirical research indicate that in the sample data of hand, there are statistically significant relationships between discretionary accruals and gross margin and return of assets coefficients. This remark may be important, among others, for stock exchange investors who have been attracting the attention of the WSE-clothes sector index for years due to the above-average rate of return.